In-vitro studies on cultural characterization of a repository of local isolates of Trichoderma spp. from Madhya Pradesh - S.K. TRIPATHI and R.K. TIWARI, ASHISH KUMAR, A.K. JAIN, JAHAAR SINGH (Indian Phytopathology, 2016)
Fungal species belonging to the genus Trichoderma are worldwide in occurrence and easily isolated from soil, decaying wood and other forms of plant organic matter. In recent years, the use of indigenous Trichoderma isolates has been suggested as a method to counter some of the factors responsible for this inconsistency in performance. Keeping this in present investigation was carried out on a set of forty isolates of Trichoderma isolates, isolated from 40 locations of 62 blocks from 14 districts of Madhya Pradesh. The cultural characteristics of the isolates were significantly variable from each other. Conidiation was predominantly effuse and conidial/colony colour change was observed of different shades like light green, dark green-white, light green-white, yellow green and white with aerial, sub-aerial and submerged-aerial type of growth pattern. Among 40 isolates of Trichoderma, one isolate of Trichoderma T23 was producing completely yellow colour in petriplate growth which was observed not only from back side of petriplate but also from the front side growth in petriplate.